Natural course of noncurative endoscopic resection of differentiated early gastric cancer - Ahn, J. Y.; Jung, H. Y.; Choi, J. Y.; Kim, M. Y.; Lee, J. H.; Choi, K. S.; Kim, D. H.; Choi, K. D.; Song, H. J.; Lee, G. H.; Kim, J. H.; Park, Y. S. (Endoscopy, 2012)
Background and study aims: Following noncurative endoscopic resection of early gastric cancer (EGC), the patient should be observed when the underlying disease is severe, the patient is elderly, or the patient refuses further treatment. The aim of this study was to analyze the clinical outcomes of patients with differentiated EGC who underwent noncurative endoscopic resection without additional treatment.Patients and methods: Included patients underwent noncurative endoscopic resection for differentiated EGC without additional treatment at the Asan Medical Center between July 1994 and January 2009. Clinical and oncological outcomes were analyzed. Results: A total of 159 patients were included in the analysis. The median follow-up period was 33 months (interquartile range [IQR] 22 – 52 months). In total, 40 patients died (25.2 %) – 3 due to stomach cancer, 34 due to other causes, and 3 from unknown causes; the median survival time after endoscopic treatment for these patients was 27.5 months (IQR 13.8 – 48.3 months). Multivariate analysis showed that the rates of underlying disease (P < 0.001) and lymphovascular invasion (P = 0.005) were higher among the 40 patients who died than among the 119 survivors. The overall 3-  and 5-year survival rates were 82.9 % and 77.1 %, respectively; the rates of the patients with lymphovascular invasion were 61.9 % and 42.4 %, respectively, and the rates of patients without lymphovascular invasion were 86.1 % and 81.8 %, respectively (P < 0.001).Conclusions: Additional treatment provides fewer benefits to patients who do not have long life expectancies. Additional surgery can be considered for patients with lymphovascular invasion because of its high mortality rate; however, the benefits and risks of surgery should be considered carefully.